Pengaruh DER dan NPM terhadap ROA pada Perusahaan Subsektor Transportasi yang terdaftar di Bursa Efek Indonesia Periode 2021-2025 - Nabila Herlina Putri; Muhammad Suparmoko; Ende Ende (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine how the Debt-to-Equity Ratio (DER) and Net Profit Margin (NPM) impact Return on Assets (ROA) of transportation subsector companies listed on the Indonesia Stock Exchange from 2021 to 2025. The study employed a causal associative method with a quantitative approach and panel data regression analysis. The research sample was determined using a purposive sampling technique, resulting in 10 companies with 50 observations. The regression model selection was carried out using the Chow test, the Hausman test, and the Lagrange Multiplier test, accompanied by descriptive statistical analysis and classical assumption testing. The study results show that Net Profit Margin (NPM) has a positive and significant effect on Return on Assets (ROA), while the Debt-to-Equity Ratio (DER) does not significantly affect ROA. However, DER and NPM simultaneously have a significant effect on ROA. These findings indicate that a company’s ability to generate net income is a key factor influencing increased profitability, while capital structure management needs to be optimized to support improved financial performance.